Sprawozdanie z Międzynarodowej Konferencji Naukowej pt. „Ochrona wolności religijnej w krajach Europy Środkowo-Wschodniej”, zorganizowanej w ramach Sieci Profesorskiej Europy Środkowej - Béres, Nóra; Marinkás, György (The Opole Studies in Administration and Law, 2022)
The scientific conference under the title ‘The protection of religious freedom in Central and Eastern European countries’ was held on 26 November 2021 in the Ministry of Justice of Hungary as the third element of the closing events of the Central European Professors’ Network. The event hosted a book launch as well: the members of the research group titled ‘Freedom of conscience and religion in Europe’ presented their book entitled ‘Religious Symbols in the Public Sphere’ which summarizes their results. Professor Sobczyk, the head of the research group, introduced the two main issues which the research group focused on, namely: ‘the presence of religious symbols in public space’ and ‘protection of religious belief in East-Central European countries’